Gentamicin concentration gradients in scala tympani perilymph following systemic applications - Hahn, Hartmut (2013)
In prior studies it was shown that round window membrane (RWM) application of gentamicin produced a robust baso-apical concentration gradient in the perilymph of scala tympani (ST) with peak concentrations in the basal turn of ST. These gradients potentially contribute to the clinical efficacy and safety of intratympanic gentamicin applications for the treatment of Meniere’s disease. The present study aimed to establish the distribution of gentamicin along ST perilymph after systemic applications. Gentamicin sulfate was applied intravenously in the amounts of 100, 300 and 600 mg/kg/bw over a period of three hours or as a 300 mg/kg/bw subcutaneous bolus injection. Three and five hours after the start of the application perilymph of ST was aspirated from the cochlea apex of the right and left cochlea, respectively. Ten sequential 1 μL-perilymph samples from the apex of each cochlea were quantitatively analyzed using a fluorescence polarization immunoassay. In contrast to local RWM delivery, systemic application of gentamicin resulted in highest perilymph levels in the apex of the cochlea with decreasing concentrations towards the basal regions of ST. The absolute gentamicin concentrations increased with amount of drug applied and time before sampling. While the basal-apical gradient measured after local drug applications to the RW niche is likely the result of the direct uptake of drugs into the perilymph of the ST, distribution by diffusion and a very low perilymph flow towards the cochlear apex, computer simulations suggested that the apical-basal gradient observed with these systemic applications can be explained by higher entry rates of gentamicin in the apex compared to the basal turns of the cochlea. It is also possible that gentamicin enters perilymph indirectly from blood via the endolymph. In this case the faster kinetics in apical turns could be due to the smaller cross-sectional area of scala tympani relative to endolymph in the apical turns.